(3LhGeY aj GdBKGQ GdYdhjIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3LhG eY ai GdBKGQ GdYdhjI bGd Cf GdMceG GdChdjf PcQhG JQcjH gPG GdYGde hWHbGJg s
(3BNQgG (B:s
(3Gdbhd ai GdeLQI ajg chGcH cKjQI eJbGQHI eVjFI hZjQ eVjFI aEPG SWY VhAgG ai GdghGA GdedJgH Je LhGeY cJGH GdBKGQ GdYdhjI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGHYI hGdYTQhfs
(3HBNQgG aGFOI dMfjf Hf GSMGb ef cJGHg GdeYQha HGdeSGFds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs